2013
DOI: 10.1007/s00436-013-3620-z
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of lethal giant larvae (Lgl) protein in the tegument and negative impact of siRNA-based gene silencing on worm surface structure and egg hatching in Schistosoma japonicum

Abstract: Lethal giant larvae (Lgl) are an evolutionarily conserved tumor suppressor present in fungi and animals. It plays an essential role in establishing apical-basal cell polarity, cell proliferation, differentiation, and tissue organization. Here, we report the presence of Lgl gene in the blood fluke Schistosoma japonicum (SjLgl) (GenBank: KF246684). SjLgl protein was mainly distributed in the unique surface tegument structure by immunofluorescence microscopic staining. Using a simple soaking method, a short inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…Recent studies indicate that the presynaptic Lgl scaffold facilitates the assembly of active zone fusion sites to regulate synaptic vesicle cycling [8]. In Schistosoma japonicum , Lgl plays an important role in the development of tegument as demonstrated by RNA interference (RNAi) [23]. …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that the presynaptic Lgl scaffold facilitates the assembly of active zone fusion sites to regulate synaptic vesicle cycling [8]. In Schistosoma japonicum , Lgl plays an important role in the development of tegument as demonstrated by RNA interference (RNAi) [23]. …”
Section: Introductionmentioning
confidence: 99%
“…The Scribble polarity module is composed of Scribble, lethal giant larvae (Lgl) and discs large (Dlg), which are well conserved across species from worms and flies to mammals [41], [58]. Recently, it has been shown that the S. japonicum Lgl protein is localized in the worm tegument and knockdown of this gene can significantly deform the surface structure of adult worm and impair egg hatching [59]. To some extent, these data may reveal the potential function of the Scribble polarity module in S. japonicum .…”
Section: Resultsmentioning
confidence: 99%
“…Based on our RNA interference experiments, we think LGL plays important roles in the development of S . japonicum embryos [20]. Additionally, we found that the partial sequence from 1866–2711 bp of Sjlgl is conserved in mammalian lgl genes; thus, its potential as a vaccine candidate was investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Evolutionarily conserved homologs of lgl have been identified in many species, including human, mouse, and worm [1719] and, in our earlier study, we found that downregulation of the Sjlgl gene affects not only egg hatching but also parasite morphology and that SjLGL mostly localizes to the tegument of adult S. japonicum , even though SjLGL does not contain a signal peptide or transmembrane domain [20]. In this study, we evaluated SjLGL as a candidate schistosomiasis vaccine.…”
Section: Introductionmentioning
confidence: 98%